2005
DOI: 10.1097/00042737-200512000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic pancreatic duct stenting for relief of pancreatic cancer pain

Abstract: PD stenting achieved significant pain relief and short-term improvement of the quality of life in the majority of patients with PD obstruction due to pancreatic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…Pancreatic duct obstruction resulting from the compression of pancreatic tumor causes pancreatic duct dilatation and increased pressure, thus inducing pancreatic hypertensive pain. A similar study confirmed that PD stenting achieved significant pain relief and short-term improvement of the quality of life in the majority of patients with PD obstruction due to pancreatic carcinoma (Wehrmann et al, 2005). In the present study, a large amount of pancreatic juice mixed with white protein plugs was seen after pancreatic duct drainage in the dilated duct patients.…”
Section: Discussionsupporting
confidence: 88%
“…Pancreatic duct obstruction resulting from the compression of pancreatic tumor causes pancreatic duct dilatation and increased pressure, thus inducing pancreatic hypertensive pain. A similar study confirmed that PD stenting achieved significant pain relief and short-term improvement of the quality of life in the majority of patients with PD obstruction due to pancreatic carcinoma (Wehrmann et al, 2005). In the present study, a large amount of pancreatic juice mixed with white protein plugs was seen after pancreatic duct drainage in the dilated duct patients.…”
Section: Discussionsupporting
confidence: 88%
“…Fentanyl side effects were not noted in our series, possibly because of the low dose (<0.5 mcg/kg, mean dose = 36 mcg) administered compared with that in other studies [7,32,33]. Indeed, alterations in the saturation oxygen level were not noted in the Fentanyl group, a finding consistent with the low fentanyl dose used because desaturation episodes seem to be dose-related [11,20,23].…”
Section: Discussionsupporting
confidence: 82%
“…Various pain scores use a 0-10 point scoring system as part of their evaluation. An example is the Brief Pain Inventory, which has been validated in a number of different languages and for evaluation of pain in endoscopic series [25,32].…”
Section: Methodsmentioning
confidence: 99%
“…The main indication for pancreatic ductal stenting is "obstructive" pain related to meals in patients with a dilated main pancreatic duct beyond a stricture. However, this procedure is rarely used and the literature suggests that at most 15% of patients will have symptoms that may benefit from this intervention [14].…”
Section: Endoscopic Stenting Of Biliary and Pancreatic Obstructionmentioning
confidence: 99%